Analisis Pengendalian Mutu pada Industri Kerudung - Upah, Upah; Saori, Sopyan; Hasan Jaelani, Mochamad Maulana; Wahyuni, Wahyuni; Ghartiwa, Ghivari Lughi (Ridwan Institute, 2021)
The purpose of this research is to analyze the defects of veil products by pareto diagram method and cause and effect, data analysis used is primary data analyzed based on check sheet and made pareto diagram and causal diagram. This research method uses primary data that is then analyzed based on check sheets and pareto diagrams and made causal diagrams, the results of this study showed that the production that failed in UMKM ANHA Store is an inappropriate color as much as 40% of the total number of failed products. After that followed by a wrinkled cloth by 60%. By using a causal diagram it can be concluded that the main factors that cause damage or incompatibility in the manufacture of the veil are people and methods.